DISTRIBUSI BAHAN ORGANIK DI BENDUNGAN CIRATA - Soetrisno, Yudhi (Jurnal Hidrosfir Indonesia, 2009)
It has been widely known that the Cirata reservoir has beenheavily polluted by waste from aquaculture and Industry. Thisresearch was conducted to determine the spread of organic matterin the waters of the Cirata reservoir The result revealed that Cirata reservoir has heavily pollutedby organic waste, so since the year 1997 has become a hypertrophicwaters, and until the year 2003 the situation has not changed. If thepollutant load is not also decrease the Cirata reservoir feared wouldturn into